Knowledge of AIDS and Risky Sexual Behaviors among Athletes - Butki, Brian D.; Anderson, Mark B.; Heyman, Steven R. (My University, 1996)
This research investigated sexual behaviors and AIDS knowledge for 381 students, athletes (n=246) and nonathletes (n=135), at a rural university. Nonathletes and athletes scored similarly on an AIDS knowledge test, but differed in reported risky sexual behavior. Athletes reported more behavioral changes after Magic Johnson's HIV-related retirement, but they still reported having more sexual partners per year than did nonathletes. The groups did not differ in condom use. By engaging in such risky behaviors, athletes may be more susceptible to sexually transmitted diseases like AIDS. Athletes (and nonathletes) continue to engage in unsafe sexual behaviors even while in possession of adequate knowledge of the risks. These results support previous research that has found that knowledge is not a valid predictor of sexual behavior (Ehde et al., 1995; Hays & Hays, 1992, Walters, 1992). Implications for athletic counselors were discussed.
Keywords: HIV/AIDS; risky behavior